Toxoplasma gondii: Effects of diphenyl diselenide in experimental toxoplasmosis on biomarkers of cardiac function - Machado V.S. (2016)
© 2016 Elsevier Inc.This study aimed to investigate the effects of diphenyl diselenide (PhSe)2 to treat mice experimentally infected by Toxoplasma gondii on seric biomarkers of cardiac function (creatine kinase, creatine kinase MB, troponin, and myoglobin), and lactate dehydrogenase, as well as to evaluate the enzymatic activity of creatine kinase (CK) and adenylate kinase (AK) in heart tissue. For the study, 40 female mice were divided into four groups of 10 animals each: the group A (uninfected and untreated), the group B (uninfected and treated), the group C (infected and untreated) and the group D (infected and treated). The inoculation was performed with 50 cysts of T. gondii (ME-49 strain). Mice from groups B and D were treated at days 1 and 20 post-infection (PI) with 5 μmol kg-1 of (PhSe)2 subcutaneously. On day 30 PI, the mice were anesthetized and euthanized for blood and heart collection. As a result, it was observed a decrease in AK activity (P < 0.01) in the heart samples of groups C and D compared to the group A. Cardiac CK increased in the group C compared to the group A (P < 0.01). CK levels increased in infected mice (the group C) compared to other groups (A and D). Regarding CK-MB level, there was a decrease in the group D compared to the group B, without statistical difference compared to control groups (A and C). It was observed an increase on myoglobin in groups C and D, differently of troponin, which did not show statistical difference (P < 0.05) between groups. Mice from the group C showed an increase in lactate dehydrogenase (LDH) levels compared to other groups (A, B, and D). Histopathological evaluation of heart samples revealed necrosis, hemorrhagic regions and inflammatory infiltrates in mice from the Group C, differently from the group D where animals showed only inflammatory infiltrates. Based on these results we conclude that the (PhSe)2 had a protective effect on the heart in experimental toxoplasmosis by modulating tissue and seric CK activity, and avoiding an increase on seric LDH levels, probably due to the antioxidant effect of this compound.